Americanness - Bronner, Simon J., author.
1 online resource
Keywords: Americanness: Inquiries into the Thought and Culture of the United States analyzes several core themes that connect Americans because of, and despite, their pronounced diversity. The book investigates shared ideas and ideals, such as individualism, mobility, materialism, and future-orientation, that drive an overarching American worldview. Simon J. Bronner begins with ideas of space and time as they formed and changed through the history of the United States, before moving to the emergence of modern American culture. He examines reasons America is characterized as having a "victory culture" that extends to the American legal, military, and business complexes. This victory culture is further analyzed by looking at the country's relationship with the game of football--asport that thrives in America but has not caught on in other countries. Finally, the volume probes American consumerism driven by a desire for individual prosperity in a supposedly egalitarian society. Using interdisciplinaryapproaches drawn frompsychology, sociology, ethnology, and history, Bronner seeks explanations for people invoking, and evoking, ideas that they perceive as American. This book would be an invaluable addition to courses on American history, sociology, cultural studies, and American studies.